Location assisted proactive channel in heterogeneous Cognitive Radio Network - Jaffar, Jasrina (Universiti Teknikal Malaysia Melaka (UTeM), 2016)
Cognitive Radio Network is an emerging technology to increase spectrum efficiency by intelligently accessing the spectrum in an opportunistic manner. The secondary user must sense every spectrum band available in order to prevent harmful interference to primary user. However, in heterogeneous environment, spectrum opportunity varies when the secondary user is mobile according to its’ geographical location. There is a certain transmission region surrounding the primary users where their transmission ranges will not exceed which therefore provides a platform for secondary user to define new policies to capture spectrum opportunities. Therefore, in this paper, we explored and proposed a proactive based spectrum decision framework based on secondary users mobility to capture more spectrum opportunities. The results showed significant improvements in throughput and switching performance when localization is inherited in the cognitive radio system.